Development of creativity. A basic guide for psychologists - Solf Zárate, Arturo (2022)
The present work seeks to increase the interest of psychologists to promote the creativity of people, in the specialties of Organizational, Clinical, and Educational psychology. He highlights the application of mindfulness and recommends learning about “lateral thinking” useful for creative problem solving. The document is mainly oriented for students of the professional career of psychology